Organizational commitment in Portuguese Higher Education Teachers - Ribeiro, Maria Isabel (2022)
Higher education institutions are at the base of the social and economic development of Economies, in the training of human resources and in the evolution and expansion of scientific knowledge. In this context, understanding the needs and desires of teachers and other employees is essential to ensure the growth of organizations and even their survival. In fact, organizational commitment is essential to obtain high levels of performance and to determine the success of institutions. This research aimed to determine the level of organizational commitment of teachers in a Portuguese Public Higher Education institution and to identify factors that contribute to reduce the level of organizational commitment so that improvement measures can be implemented. In this sense, a cross-sectional study was carried out based on the application of a questionnaire that included the three-dimensional model of organizational commitment (affective, calculative and normative) developed in 1991 by Meyer and Allen [1], resulting in 76 responses. Most respondents were female, belonged to the professional category of Auxiliary Professor (51.3%) and had an indefinite relationship with the organization (61.8%). Teachers exercised their teaching and research functions in several scientific areas, namely, Technologies and Management (26.3%), Health (25.0%), Education (23.7%), Agriculture (21.1%) and Communication, Administration and Tourism (3.9%). The age of the teachers was between 30 and 66 years old and the average was 49.5 years old (SD = 8.05). The service time of these teachers was, on average, 20 years (SD = 10.18). Globally, the length of service ranged from 2 to 43 years, with the maximum number of years in the same professional category reaching 30 years. The results obtained reflect a good internal consistency of the model (Cronbach's Alpha > 0.7), registering a moderate organizational commitment in the three subscales (affective, calculative and normative) and in the global model. Seven factors were identified that most contribute to reduce the level of organizational commitment. Four are part of the normative dimension and three are associated with the calculative dimension. Basically, there are teachers who do not leave the organization because they feel an obligation to remain there, not only because of the people they work with, but also because they feel that they have already given a lot of themselves to the organization and, therefore, they do not even consider the possibility of working elsewhere. On the other hand, the lack of available employment alternatives and the personal sacrifice of starting all over again, perhaps due to their age, makes teachers adapt to the situation. Based on the results obtained, it is recommended the implementation of convincing, productive and effective measures by the Management of the Public Higher Education Institution and the Central Government. Specifically, these measures must include the evolution of the teaching career, fair and deserved, in an attempt to reinforce normative and calculative commitment levels, with the objective of stimulating the prosperity of teachers and organizational productivity in order to guarantee the success of the organization and reach levels of excellence in the services provided to the community and, in particular, to students.